A Case Study on Neo-Wave Cinema Based on Feminism - Prabhu, Anthony Kimton (International Journal of Computer Sciences and Engineering, 2025)
The aim of the research paper is to study about the portrayal of women in cinema. Also, it aimed to analyse the changing mind set of the young budding directors from the cinema industry. The emerging directors of our current film industry are very well aware of the portrayal of women which makes them to form a well-scripted for their film story. In this research, these young directors of cinema industry with a feministic approach in their movies are interviewed and analysed for the research. The social issues faced by women in both psychological and physical aspect is been brought to limelight and bravely disclosed in their films. The main films which are been discussed for this research are IRAIVI, THARAMANI and ARUVI which is been released in the year of 2016, 2017 and 2018 consecutively. These directors are been categorised under neo wave film making directors of cinema industry where they portray a favourable opinion regarding the strong characterisation of women and their struggle against gender bias. Henceforth these types of films had created a reflection of rational thoughts among the viewers and audiences to understand the present scenario of social issues against women prevailing in the authoritarian society. This research tries to provide awareness for the future budding directors about the importance of social touch in a movie in connection with the entertainment in the whole form as infotainment